2016
DOI: 10.1371/journal.pone.0155204
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment of Pharmaceutical Care in the Management of Hypertension and Coronary Risk Factors after Discharge

Abstract: IntroductionAlmost 50% of the 17.5 million deaths worldwide from cardiovascular disease have been associated with systemic arterial hypertension (SAH). Into this scenario, Pharmaceutical Care (PC) has been inserted in order to improve the management of SAH and reduce its risks.ObjectiveTo evaluate the outcomes and healthcare assistance achieved after discharge of hypertension patients from the PC program.MethodsThis is a quasi-experimental study with historical controls. Retrospective data collection from 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
12

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 32 publications
3
28
0
12
Order By: Relevance
“…In the period before taking pharmaceutical care 54.4%, 79.0%, and 27.3% of patients presented satisfactory levels of systolic (SBP), diastolic (DBP) blood pressure, and lipid profile, respectively. During the two-year observation period (2010- -2012) after the pharmaceutical intervention, the percentages were 93.0% for SBP and DBP (p < 0.001) and 60.6% for total-cholesterol (p < 0.001) [25]. Similar conclusions can be derived from another, recently published, randomised clinical trial.…”
Section: Pharmaceutical Care Of Cardiology Patientssupporting
confidence: 78%
“…In the period before taking pharmaceutical care 54.4%, 79.0%, and 27.3% of patients presented satisfactory levels of systolic (SBP), diastolic (DBP) blood pressure, and lipid profile, respectively. During the two-year observation period (2010- -2012) after the pharmaceutical intervention, the percentages were 93.0% for SBP and DBP (p < 0.001) and 60.6% for total-cholesterol (p < 0.001) [25]. Similar conclusions can be derived from another, recently published, randomised clinical trial.…”
Section: Pharmaceutical Care Of Cardiology Patientssupporting
confidence: 78%
“…A maior parte dos estudos brasileiros, quando se remete à prática dos serviços farmacêuticos clínicos, relaciona a sua operação por meio do seguimento/acompanhamento farmacoterapêutico, caracterizando-o como atividade mais mencionada e estudada (Lyra-Júnior et al, 2007a, 2007bFoppa et al, 2008;Provin et al, 2010;Obreli-Neto et al, 2011a, 2011b, 2015Plaster et al, 2012;Mourão et al, 2013;Firmino et al, 2015;Cazarim et al, 2016).…”
Section: Os Tipos De Serviços Farmacêuticos Clínicos Realizados Na Atunclassified
“…Assim, a literatura atual já reporta a existência simultânea, a importância e a interlocução dos diversos serviços clínicos nos programas de cuidado farmacêutico aos usuários das redes de atenção à saúde (Lyra-Júnior, Marcellini e Pelá, 2008;Cazarim et al, 2016;Melo e Castro, 2017;Javadi et al, 2016;Ndefo et al, 2017).…”
Section: Continuação Quadrounclassified
“…Many studies have presented the theme of economic evaluation focused on the care provided by the pharmacist, such as pharmaceutical care, which uses methods such as MTM and patient empowerment [22,44]. Pharmaceutical care in a program for the elderly with T2DM and systemic arterial hypertension followed in primary health care in a municipality in the interior of the state of São Paulo, showed that the implementation of pharmaceutical care does not add significant costs to the health service when compared to the results of the best outcomes achieved in patient care [35].…”
Section: Costs Associated With the Treatment Of Diabetes Mellitusmentioning
confidence: 99%
“…The WHO estimates that the costs of loss of productivity of DM patients can exceed up to five times the direct costs of this disease [20,36]. It is seen that empowerment of the diabetic patient improves glycemic control and, consequently, reduces the incidence of DM complications over time, which is the main aspect to reduce costs with the treatment of the disease; empowerment of the diabetic patient can be considered an efficient health technology for health systems.Many studies have presented the theme of economic evaluation focused on the care provided by the pharmacist, such as pharmaceutical care, which uses methods such as MTM and patient empowerment [22,44]. Pharmaceutical care in a program for the elderly with T2DM and systemic arterial hypertension followed in primary health care in a municipality in the interior of the state of São Paulo, showed that the implementation of pharmaceutical care does not add significant costs to the health service when compared to the results of the best outcomes achieved in patient care [35].…”
mentioning
confidence: 99%